Whole genome sequencing and analysis on the trios of the Che Wong and Semai:understanding the medico-genomic association / Rose Iszati Ismet Nayan - Ismet Nayan, Rose Iszati (Institute of Graduate Studies, UiTM, 2017)
As to date, there is no report on the architecture of the whole genomes of the unique Orang Asli subtribes in Peninsular Malaysia. The Che Wong was selected as the group of interest as they have a dwindling population of 651, while the Semai Orang Asli with a population number of 51,313 was selected as the control group. The Semai is the largest sub-tribe of the Senoi which is also the largest group amongst the Orang Asli. This study aims to understand the variation in genomics composition of the Che Wong and Semai Orang Asli by a deep and systematic characterization of the genome through development of an in-house bioinformatics pipeline. The disease risk and protection conferred by genetic traits were explored via sequencing the whole genome of a trio family of both the Che Wong and Semai subtribes. The Che Wong and Semai genomes were sequenced and mapped to the human reference genome (hg19) with an average coverage of 44.1x and 43.0x, respectively. A total of ~6.23 million and ~6.18 million variants were identified for the Che Wong and Semai trios, respectively…